2012
DOI: 10.1007/s10681-012-0643-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a core set of SSR markers for the characterization of Gossypium germplasm

Abstract: Molecular markers such as simple sequence repeats (SSR) are a useful tool for characterizing genetic diversity of Gossypium germplasm. Genetic profiles by DNA fingerprinting of cotton accessions can only be compared among different collections if a common set of molecular markers are used by different laboratories and/or research projects. Herein, we propose and report a core set of 105 SSR markers with wide genome coverage of at least four evenly distributed markers per chromosome for the 26 tetraploid cotton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…PIC values provide an estimation of marker power by considering both the number of alleles at a locus and the relative frequencies of those alleles in the population under study (Pei et al, 2010). Our observed Table 1. average PIC value was 0.23, whereas the average PIC value of a core set of SSR markers for Gossypium species ranged from 0.0 to 0.82 (Yu et al, 2012). One of the findings of the present study is that the most informative markers are CIR246 with 0.749 PIC value among fiber quality linked SSR markers and DPL513 with 0.724 PIC value among tested DPL series primers.…”
Section: Discussionmentioning
confidence: 50%
“…PIC values provide an estimation of marker power by considering both the number of alleles at a locus and the relative frequencies of those alleles in the population under study (Pei et al, 2010). Our observed Table 1. average PIC value was 0.23, whereas the average PIC value of a core set of SSR markers for Gossypium species ranged from 0.0 to 0.82 (Yu et al, 2012). One of the findings of the present study is that the most informative markers are CIR246 with 0.749 PIC value among fiber quality linked SSR markers and DPL513 with 0.724 PIC value among tested DPL series primers.…”
Section: Discussionmentioning
confidence: 50%
“…The PIC values were also more elevated than those found for cultivars (Yu et al, 2012;Hinze et al, 2015;Moiana et al, 2015) showing discriminative potential conferred by 12 loci. The large genetic basis of mocó cotton is due to multiple contributions during domestication and selection (Moreira et al, 1995), including introgressions (Freire and Moreira, 1991;Lacape et al, 2007) and selection by local farmers (Freire et al, 1990;Menezes et al, 2010).…”
Section: Discussionmentioning
confidence: 67%
“…A core set of SSR markers was evaluated for DNA polymorphisms in 12 genotypes of 6 Gossypium species, collectively known as the cotton marker database panel. The results indicated that the core marker set was robust for characterization of Gossypium germplasm (Yu et al, 2012a). Although polymorphism levels for these primers are high in different Gossypium germplasms, levels are low in cultivated varieties such as upland cotton.…”
Section: Introductionmentioning
confidence: 94%
“…Cultivated cotton is the world's leading fiber crop and the second most important oilseed crop (Yu et al, 2012a). The authorization and release of high-quality cultivars is important in agricultural production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation